Environmental Factors Modulating the Stability and Enzymatic Activity of the Petrotoga mobilis Esterase (PmEst) - Lopes, Jose L. S.; Yoneda, Juliana S.; Martins, Julia M.; DeMarco, Ricardo; Jameson, David M.; Castro, Aline M.; Bossolan, Nelma R. S.; Wallace, B. A.; Araujo, Ana P. U. (PLOS ONE, 2016)
Enzymes isolated from thermophilic organisms found in oil reservoirs can find applications in many fields, including the oleochemical, pharmaceutical, bioenergy, and food/dairy industries. In this study, in silico identification and recombinant production of an esterase from the extremophile bacteria Petrotoga mobilis (designated PmEst) were performed. Then biochemical, bioinformatics and structural characterizations were undertaken using a combination of synchrotron radiation circular dichroism (SRCD) and fluorescence spectroscopies to correlate PmEst stability and hydrolytic activity on different substrates. The enzyme presented a high Michaelis-Menten constant (KM 0.16 mM) and optimum activity at 55°C for p-nitrophenyl butyrate. The secondary structure of PmEst was preserved at acid pH, but not under alkaline conditions. PmEst was unfolded at high concentrations of urea or guanidine through apparently different mechanisms. The esterase activity of PmEst was preserved in the presence of ethanol or propanol and its melting temperature increased 8°C in the presence of these organic solvents. PmEst is a mesophilic esterase with substrate preference towards short-to medium-length acyl chains. The SRCD data of PmEst is in agreement with the prediction of an α/β protein, which leads us to assume that it displays a typical fold of esterases from this family. The increased enzyme stability in organic solvents may enable novel applications for its use in synthetic biology. Taken together, our results demonstrate features of the PmEst enzyme that indicate it may be suitable for applications in industrial processes, particularly, when the use of polar organic solvents is required.